2021
DOI: 10.1108/jarhe-09-2020-0302
|View full text |Cite
|
Sign up to set email alerts
|

Lecture-based, virtual reality game-based and their combination: which is better for higher education?

Abstract: PurposeThis paper presents an educational virtual reality (VR) game and experiments with different methods of including it into the teaching process. The purpose of this research study is to discover if immersive VR games can be used as an effective pedagogical tool if blended with traditional lectures by assisting learning gain, memory and knowledge retention while increasing edutainment value.Design/methodology/approachThis research design comprises three different methods of learning: lecture-based involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Since previous research demonstrated that males are more habituated with the in-game controls as they generally play computer games leisurely, attention is required for user-friendly designs inclusive gamification (Hainey et al, 2013). Sanzana et al (2021) discuss an interesting method of exploiting a first-person based story-mode gamification approach for increasing student engagement and edutainment. It is important to research and employ useful gamified elements in a virtual learning environment to create more active learning as it begets the best outcomes (Nørgaard et al, 2019).…”
Section: Gamified Approach In Virtual Labsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous research demonstrated that males are more habituated with the in-game controls as they generally play computer games leisurely, attention is required for user-friendly designs inclusive gamification (Hainey et al, 2013). Sanzana et al (2021) discuss an interesting method of exploiting a first-person based story-mode gamification approach for increasing student engagement and edutainment. It is important to research and employ useful gamified elements in a virtual learning environment to create more active learning as it begets the best outcomes (Nørgaard et al, 2019).…”
Section: Gamified Approach In Virtual Labsmentioning
confidence: 99%
“…Studies have shown that gamified approaches increase edutainment value and knowledge retention compared to plain knowledge sharing (Sanzana et al, 2021). With appropriate gamification of lab simulations, students will be able to understand certain topics better as they go through the experiments themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Surely, this relatively new activity, namely virtual lecture, is something new for the world of education [1]. Many obstacles occur such as difficulty in accessing internet signals for students in remote villages, boredom of learning from home, lecturers who only gave PPT without explaining again and others.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual Reality has a continual virtual world that generally requires external expensive devices such as headsets and controllers. The user has to wear the headset and take the controllers to completely immerse himself/herself in the virtual world with sight and sound (Sanzana, et al, 2021). Besides, virtual reality has an aspect of alienation and is not suitable for many individuals as they might feel discomfort.…”
Section: Introductionmentioning
confidence: 99%